2017
DOI: 10.4103/nmj.nmj_265_14
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and outcome of sinonasal tumors in a Nigerian Tertiary Hospital – 6-year review

Abstract: Background:Sinonasal tumor is an uncommon tumor in Nigeria, but the burden of the disease in terms of morbidity and mortality is on the increase. The aim of this study is to evaluate the pattern of presentation and outcome of sinonasal tumor in our center.Methodology:This was a retrospective review of all the patients with sinonasal cancer seen in Ear, Nose, and Throat Department of the hospital between January 2008 and December 2013. The patients' biodata, clinical presentation, stage of the disease at presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
5
7
0
Order By: Relevance
“…In this study the commonest disease conditions found were rhinosinusitis followed by sinonasal and nasopharyngeal tumors similar to other findings [6,7]. The commonly seen clinical features of sinonasal diseases in the present study were nasal blockage, rhinorrhea and epistaxis as was also documented by other works [13]. In addition those with advanced disease extending to congruent structures such as the eye/orbit had features such proptosis and facial asymmetry [14,18,19] Majority of the tumours/ masses were seen in advanced stages as already documented by others and some of the factors deduced for this included; self-medication, quackery, poverty and fact that the sinonasal region is an area that appears hidden [13,16,17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study the commonest disease conditions found were rhinosinusitis followed by sinonasal and nasopharyngeal tumors similar to other findings [6,7]. The commonly seen clinical features of sinonasal diseases in the present study were nasal blockage, rhinorrhea and epistaxis as was also documented by other works [13]. In addition those with advanced disease extending to congruent structures such as the eye/orbit had features such proptosis and facial asymmetry [14,18,19] Majority of the tumours/ masses were seen in advanced stages as already documented by others and some of the factors deduced for this included; self-medication, quackery, poverty and fact that the sinonasal region is an area that appears hidden [13,16,17].…”
Section: Discussionsupporting
confidence: 91%
“…it is rare in children [11] and seen more in ages >20years [12]. Some of these diseases are known to have high burden of morbidity and mortality with clinical presentations depending on the site and extension of the disease [13]. The commonly documented features include nasal obstruction, discharge, facial swelling, epistaxis, nasal mass, headaches [14,15,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We studied different occupational exposures among the study population and we surprisingly found domestic workers were the most vulnerable groups among all (20%) followed by agricultural workers and manual labour (12.5% each). This finding is very similar with the findings by B. S. Alabi et al 9 They conducted a research on sinonasal malignancy in the Nigerian tertiary hospital over 6 years where they similarly found largest group (29%) was exposed to indoor cooking and wood dust most likely in the form of firewood for cooking. In addition, cigarette smoking (18%) was found to be an important risk factor in their study which is similar to our results.…”
Section: Discussionsupporting
confidence: 90%
“…Chemotherapy is of only palliative value as suggested by several series. 9 These factors must be taken into account while planning treatment of a case of ACC.…”
Section: Discussionmentioning
confidence: 99%